Analysis of Parking Capacity and Road Performance in Cileungsi-Bogor Market - Muhammad Isradi; Putri Rahayu; Amar Mufhidin; Widodo Budi Dermawan; Joewono Prasetijo (Journal of World Conference (JWC), 2022)
Cileungsi Market which is located on Jln Raya Narogong, Cileungsi Kidul Village, Rt. 03/06 Kec. Cileungsi Kab. Bogor. As a trading center. Therefore, the Cileungsi Market area needs to optimize and improve the performance of the area itself. One of the facilities that need to be optimized for its performance is the parking lot. This study aims to analyze the volume of vehicles entering and leaving the Cileungsi market area, to analyze the characteristics and parking needs of the Cileungsi Market area, to provide parking management solutions to maximize the existing parking capacity in the Market area, to determine the performance of roads in the area. cileungsi market. The method used in this research is a field survey by recording the types of vehicles entering and leaving the parking area and taking data on the condition of the roads in the Cileungsi market area. The results of the analysis of the maximum parking volume of 384 cars and 2174 motorcycles Maximum accumulation of 92 cars and 293 motorcycles. The average parking duration for cars is 1.07 hours/vehicle and 1.45 hours/vehicle for motorbikes. The maximum parking turnover rate is 1 vehicle/SRP/time for cars and 1 vehicle/SRP/time for motorbikes. The maximum parking index is 81.42% for cars and 73.80% for motorbikes. The results of the analysis of the performance of the Jln. Raya Narogong traffic flow and average speed is quite stable. with an average level of service or Level of Service (LOS) which is C from the average value of the Degree of Saturation, which is 0.53.